Using advocacy in social work practice : a guide for students and professionals - Scourfield, Peter (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This book explains different types of advocacy and the various ways in which advocacy is used in social work, making links with core social work concepts such as empowerment, safeguarding and rights. Tracing how the use of advocacy is mandated in professional social work guidance and codes of practice as well as in legislation such as The Care Act 2014 and the Mental Capacity Act 2005, this book: Explores definitions of advocacy, discusses what it can achieve and explains the different uses of it in social work. Covers the necessary knowledge, skills and values that social workers need in order to advocate effectively in their own practice. Discusses critically what independent advocacy is and explains why it has become an integral part of contemporary social work. Examples are provided of where independent advocacy plays an important role in different areas of social work. Explains what social workers need to know about working effectively with different types of advocate. Encourages critical reflection on the relationship between social work and independent advocacy and flags debates and issues relating to the use of advocacy in social work. Aimed at social work students and social work professionals, this book provides an excellent introduction into a topic which is highly relevant to social work, using case-studies and activities to aid understanding"--
OCLC-licensed vendor bibliographic record.
Keywords: Social advocacy; Social service; SOCIAL SCIENCE / Human Services